Effect of Y-length and biasing of lithium niobate Mach-Zehnder modulator on insertion loss and extinction ratio / Nor Hidayah Roslan, Aziati Husna Awang and Mohd Hanapiah M. Yusoff - Roslan, Nor Hidayah; Awang, Aziati Husna; M. Yusoff, Mohd Hanapiah (Universiti Teknologi MARA Press (Penerbit UiTM), 2020)
An optical modulator is a device which signalcontrolled the electro-optic effect which is used to modulate the beam of light of an optical signal. This article analyzes the performance of different structures of Mach-Zehnder Interferometer (MZI) modulator. The conventional MZI modulator high loss compare to the PCW modulator. So that we compares the performance of the photonic crystal waveguide (PCW) and conventional of Mach-Zehnder Interferometer (MZI) modulator on the lithium niobate (LinBO3).(Method)For the PCW of MZI modulator is designed photonic crystal cavity at one arm of the modulator then for the conventional MZI modulator there is a electrode at one arm of the modulator and applied voltage of 0.9 V. This project used OptiFDTD, OptiBPM software for designing the structures of both modulators and performance analysis. The performance has been analyzed based on the insertion loss, extinction ratio and the phase difference. Low insertion loss with increasing the length of Y branch for the PCW of MZI modulator compare to the conventional MZI modulator. It has highest extinction ratio 8.0521 dB compare to the conventional MZI modulator only 1.29 dB and the phase difference is bigger for the PCW of MZI modulator compare to the conventional MZI modulator to achieve the low power consumption for the optical interconnects in computer chip performance.Therefore, PCW of MZI modulator has low insertion loss and high extinction ratio to obtain good value of modulation efficiency and high phase shift to achieve better performance.